ANALISIS PENGARUH VARIABEL FUNDAMENTAL, RISIKO SISTEMATIK, DAN JENIS PERUSAHAAN TERHADAP RETURN SAHAMANALISIS PENGARUH VARIABEL FUNDAMENTAL, RISIKO SISTEMATIK, DAN JENIS PERUSAHAAN TERHADAP RETURN SAHAM - Satrio Adi Wibowo; Sudarno Sudarno (Diponegoro Journal of Accounting, 2013)
Study aimed to examine the influence of fundamental variables, systematic risk, and the type of company to manufacturing company stock return. The variables used in the study include profitability, leverage, stock performance, the annual inflation rate, and type of company.This study population is  manufacturing company listed on the Indonesia Stock Exchange (BEI) period 2009 to 2011. Type of company is divided into basic chemical manufacturing companies and non-chemical basis. So the total sample in accordance with the criteria amounted to 83 companies each year. The hypothesis tested in this study with multiple regression analysis.  The results of this study indicate that profitability and inflation does not affect the amount of manufacturing company stock returns. While variable leverage, stock performance, and the type of company affect stock return manufacturing company